2022
DOI: 10.3390/molecules27248647
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficiency of Chitosan and Its Methylated Derivative against Lentilactobacillus parabuchneri Biofilms

Abstract: Antimicrobial materials are considered potential alternatives to prevent the development of biofilm-associated contaminations. Concerns regarding synthetic preservatives necessitate the development of innovative and safe natural antimicrobials. In the present study, we discuss the in situ infrared attenuated total reflection spectroscopy (IR-ATR) investigations of the selective antimicrobial efficiency of chitosan in controlling the growth of Lentilactobacillus parabuchneri biofilms. The protonated charges of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…[ 13 , 65 , 66 ]. New materials that might prevent microbial growth are being explored [ 67 , 68 ], including the use of safe natural antimicrobial coating surfaces [ 69 ], but there remain many that are difficult to clean. The design requirements of equipment can also render effective cleaning and disinfection difficult [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 , 65 , 66 ]. New materials that might prevent microbial growth are being explored [ 67 , 68 ], including the use of safe natural antimicrobial coating surfaces [ 69 ], but there remain many that are difficult to clean. The design requirements of equipment can also render effective cleaning and disinfection difficult [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sterilized MRS medium was flushed into the system for 3 h with a delay of 5 min between measurements at a flow rate of 0.7 mL/min, which resulted in a residence time within the flow cell of ~ 150 s. After recording the conditioning film background, the MRS media were replaced with a bacterial solution (OD 600 = 0.7) for 2 h at a 0.7 mL/min flow rate with a 10 min delay between measurements. This period was optimized on the basis of the required time for initiating the attachment of L. parabuchneri biofilms at the ZnSe waveguide [ 37 , 38 ]. After 2 h of initial attachment of L. parabuchneri , sterile MRS medium was pumped again through the FTIR-ATR assembly cell for 24 h at a 0.5 mL/min flow rate.…”
Section: Methodsmentioning
confidence: 99%
“…For example, one can obtain a quaternized version of chitosan, specifically its ammonium salt, by incorporating a quaternary ammonium group into the chitosan backbone. One notable study demonstrated that a quaternized chitosan variant, N , N , N -trimethylammonium chitosan chloride, had superior antibacterial capabilities, a wider spectrum of antimicrobial activity, and an accelerated rate of bacterial cell destruction than its unmodified counterpart [ 58 , 126 , 127 ].…”
Section: Antibacterial Activity Of Chitosan and Its Derivativesmentioning
confidence: 99%